Propuesta de diseño de una planta recicladora, de residuos sólidos en la mancomunidad zona norte de los cantones, Tosagua, Junín y Bolívar - Avellán Loor, Ramón Emanuel (2022)
The purpose of this study was to design a solid waste recycling plant for the northern zone association of the cantons, Tosagua, Junín and Bolívar. For this, the types of solid waste that are generated were characterized, conducting interviews and surveys to a specific sample for each canton, in order to determine the average generation of waste in the study area, then the average density was calculated being 921, 72 kg/m3, with a waste value of 0.146 m3/day and an average per capita production of 0.8 kg/inhab*day. Then, the design of a recycling plant was carried out in the north zone commonwealth, it will have an area of 18,900 m2, this being the land chosen for the implementation and the following areas will be distributed: waste, operation, selection and weighing, storage of recycled waste and finished product storage, will have a manual sanitary landfill of 5,398 m2; taking into consideration the economic and environmental feasibility of the recycling plant, an expense of $332,800.00 was obtained, which will be recovered when the usable products are marketed and with respect to the environment through the elaboration of the Leopold matrix, a magnitude of moderate impact with a value of 2.6 which through corrective measures can be mitigated. Finally, it was obtained that the plant is characterized as a positive impact, since it will generate jobs and promote environmental awareness in the community